The Development of Performing Folk Songs Model to Develop Holistic Health in Elderly - Boonsong, Panuracht; Wanwichai, Rawiwan; Chinpong, Sureerat (Journal of Ecohumanism, 2024)
This research aims to study the problems and factors in organizing activities to promote holistic health in the elderly, Elderly Social Welfare Development Center, and to develop activities in the art of performing folk songs to promote holistic health in the elderly, Elderly Social Welfare Development Center. It is a study that aims to extract knowledge about the process of organizing activities for the elderly in order to develop a form of folk song performing arts activities to develop holistic health in the elderly as a research and development model Divided into 3 phases: Phase 1 synthesizes knowledge on organizing activities for the elderly, Phase 2 develops and evaluates traditional performing arts activities to develop holistic health in the elderly, and Phase 3 uses Folk performing arts activity format for holistic health development in the elderly. The research tool used was a structured interview form and satisfaction assessment form for organizing activities. All analysis results are presented as descriptive data and tables with explanations. The findings revealed Problems and factors in organizing activities to promote holistic health in the elderly at the Elderly Social Welfare Development Center. The researcher can summarize into two issues: 1) The current condition of organizing activities to promote the health of the elderly at the 12 Elderly Social Welfare Development Centers has three formats: ordinary elderly, particular types, and centers without elderly residents. In terms of operations for caring for and promoting the elderly, there will be an operation plan for the center that promotes the health of the elderly. There are four areas: physical, mental, and social interaction and intelligence. 2) Factors in organizing activities to promote holistic health in the elderly. The Center for the Development of Social Welfare for the Elderly found that opinions and needs for bringing in local wisdom heritage, in terms of performing arts, all four regions came to organize activities to promote the health of the elderly at all 12 Elderly Social Welfare Development Centers. There were two issues: 1) Perspectives and opinions. It was found that bringing both local performing arts and four regionally organized activities to promote the health of the elderly within the center. It is a good and exciting activity. Most elderly people enjoy fun activities, including singing and dancing. It is also a matter of Folk performing arts that can understand the emotions and feelings of the elderly very well. It also helps promote and stimulate the memory of the elderly. 2) The need to bring local wisdom and heritage. In terms of performing arts, all four regions came to organize activities to promote the health of the elderly at all 12 Elderly Social Welfare Development Centers. It was found that there was a need to organize activities to promote the health of the elderly using all Folk performing arts. The aim is to organize activities that can develop the physical, mental, social, and intellectual aspects. The results of the development of activities in the art of performing folk songs to promote holistic health in the elderly have two crucial points: 1) The uniqueness of the art of folk song performance that has an impact on society is that it reflects the culture of the community, build relationships among people in the community, have fun public relations media and self-development 2) The results of creating and developing an art activity format for performing folk songs to promote holistic health in the elderly. The researcher created and developed a folk song performance art activity model consisting of 6 elements: principles of the form, Objectives of the format, content, activities, promoting factors, and evaluation